Effects of whole-body irradiation on neonatally thymectomized mice. Incidence of benign and malignant tumors. - Anderson, R. E. (1978)
The individual and combined effects of neonatal thymectomy and whole-body irradiation on the prevalence of benign and malignant tumors in germ-free female mice of the Charles Rivers line were studied to determine if a portion of the tumorigenic effects of irradiation can be attributed to injury of the thymic-dependent component of the immune response. Neonatal thymectomy increased a) the incidence of benign and malignant tumors and b) the prevalence of multiple primary neoplasms in an individual mouse. Whole-body exposure to 700 rad at 6 weeks of age further increased th incidence of tumors, but the relative magnitude of this increase was less pronounced than in sham-operated controls. Thus, the cumulative effects of thymectomy plus irradiation are less pronounced than the sum of the individual effects. One of several possible explanations for this observation is that a portion of the carcinogenic effects of whole-body irradiation is mediated by suppression of the thymic-dependent component of the immune response.